2015
DOI: 10.1152/jn.00416.2014
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping rather than motor prediction subserves modulation of corticospinal excitability during observation of actions in real time

Abstract: Gueugneau N, Mc Cabe SI, Villalta JI, Grafton ST, DellaMaggiore V. Direct mapping rather than motor prediction subserves modulation of corticospinal excitability during observation of actions in real time. J Neurophysiol 113: 3700 -3707, 2015. First published March 25, 2015 doi:10.1152/jn.00416.2014.-Motor facilitation refers to the specific increment in corticospinal excitability (CSE) elicited by the observation of actions performed by others. To date, the precise nature of the mechanism at the basis of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In particular there was no evidence of a muscle-specific modulation of MEPs during the precision grip observation compared to the intra-task baseline. Whilst numerous other studies have established muscle-specific effects during action observation (e.g., Alaerts et al, 2009 ; Gueugneau et al, 2015 ; Bunday et al, 2016 ; Hilt et al, 2017 ; see also Naish et al, 2014 for a review), we note that sometimes these results stem from muscle by movement interactions (i.e., comparisons across movement conditions) that do not consider whether there has actually been a change relative to some other time point or baseline (Alaerts et al, 2009 ; Bunday et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular there was no evidence of a muscle-specific modulation of MEPs during the precision grip observation compared to the intra-task baseline. Whilst numerous other studies have established muscle-specific effects during action observation (e.g., Alaerts et al, 2009 ; Gueugneau et al, 2015 ; Bunday et al, 2016 ; Hilt et al, 2017 ; see also Naish et al, 2014 for a review), we note that sometimes these results stem from muscle by movement interactions (i.e., comparisons across movement conditions) that do not consider whether there has actually been a change relative to some other time point or baseline (Alaerts et al, 2009 ; Bunday et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both non-invasive and invasive studies have since pointed to the existence of similar, mirror-like activity in the human motor system, including in the primary motor cortex (M1) (Fadiga et al, 1995 ; Hari et al, 1998 ) and supplementary motor area (Mukamel et al, 2010 ). Transcranial magnetic stimulation (TMS) studies have shown that the corticospinal pathway is facilitated during action observation (Fadiga et al, 1995 ; Gangitano et al, 2001 ; Maeda et al, 2002 ; Labruna et al, 2011 ; Gueugneau et al, 2015 ), which seems consistent with the increased activity in primate premotor areas (di Pellegrino et al, 1992 ; Gallese et al, 1996 ; Kraskov et al, 2009 ), with direct cortico-cortical connections to M1, and in M1 itself (Vigneswaran et al, 2013 ; Kraskov et al, 2014 ). However, since some of those neurons in M1 included pyramidal tract neurons, the majority of which project directly to the spinal cord (Lemon, 2008 ), it remains unclear how the increased activity in the motor system during observation is prevented from producing overt movement.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitation was most prominent during Hand Shaping before the grasp, and just after the grasp itself. Previous findings in humans suggest that corticospinal excitability modulations peak at the time of observed maximal hand aperture (Gangitano et al 2001), while dynamic stages of the action are ongoing (Urgesi et al 2006(Urgesi et al , 2010, or at the time when grasp is achieved (Gueugneau et al 2015), and the peak of the observation response in macaque mirror neurons often occurs prior to, or around, the grasp (Vigneswaran et al 2013).…”
Section: Observation Of Grasp Produces Facilitation At the Spinal Levelmentioning
confidence: 95%
“…Moreover, recent studies have shown that MI increases M1 excitability, resulting in motor learning by mental practice [84], [86], [87]. In other words, motor learning can be achieved by MI practice, leading to the development of neuroplasticity in the human primary cortex (M1).…”
Section: Neuroplasticitymentioning
confidence: 99%